2011
DOI: 10.1002/jcu.20837
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of right atrial pressure using echocardiography and correlation with catheterization

Abstract: The combination of IVC diameter and collapsibility index is a simple a semiquantitative approach that might provide a better estimation of RAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 18 publications
3
42
0
1
Order By: Relevance
“…Similarly, tricuspid annular velocity has been proposed in conjunction with tricuspid inflow E-wave velocity as a predictor of RAP (RV E/A ratio), 12 but it failed to show a relevant correlation in our study population. 25 Finally, other variables (regional isovolumic relaxation time, RV E/E 0 ta , RAVI, RV Tei index, and RAEF) either were not statistically significant or had poor correlations with RAP.…”
Section: Rap and Its Potential Echocardiographic Surrogatesmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, tricuspid annular velocity has been proposed in conjunction with tricuspid inflow E-wave velocity as a predictor of RAP (RV E/A ratio), 12 but it failed to show a relevant correlation in our study population. 25 Finally, other variables (regional isovolumic relaxation time, RV E/E 0 ta , RAVI, RV Tei index, and RAEF) either were not statistically significant or had poor correlations with RAP.…”
Section: Rap and Its Potential Echocardiographic Surrogatesmentioning
confidence: 98%
“…7,12,23 It is also difficult to assess serial changes. 24,25 Patient positioning and ability to cooperate with instructions can also influence the diameter change with inspiration. Nevertheless, we demonstrated that method 1, IVCd, and IVCd%change with inspiration still had the highest correlations with RAP compared with the other methods.…”
Section: Rap and Its Potential Echocardiographic Surrogatesmentioning
confidence: 99%
“…2 To date, the IVC approach has been studied mainly for American and European populations. [3][4][5] In addition, because the size of organs is considered to vary with body size, many echocardiographic variables are indexed to body surface area (BSA). Despite the widespread use of the IVC approach for RAP assessment, the relation between BSA and IVC parameters remains unclear.…”
mentioning
confidence: 99%
“…A similar correlation (r = ? 0.56, p \ 0.05) in other cardiac diseases such as mitral valve stenosis and atrial fibrillation has been reported by Yildirimturk et al [7].…”
Section: Discussionmentioning
confidence: 61%
“…In different studies on subjects with normal anatomy, correlation of the inferior vena cava (IVC) collapsibility and the degree of central venous pressure has been confirmed [6][7][8]. However, few studies have attempted to correlate angiographic data with echocardiographic findings in patients with TCPC who have a venous system without cardiac pumping.…”
Section: Introductionmentioning
confidence: 98%